Fear of terrorism and attitudes toward refugees: an empirical test of group threat theory - De Coninck, David (Crime & delinquency, 2022)
In recent years, the co-occurrence of the migration crisis and terrorist attacks in European cities have created a strong link between refugees and asylum seekers and terrorism in the minds of many Europeans. This study investigates how attitudes toward refugees are associated with fear of terrorism. Using multilevel modelling on 1,500 Belgian citizens nested in 402 municipalities, results indicate that positive attitudes toward refugees are associated with lower terrorism fear. Adverse economic conditions at both the individual and municipal level are associated with greater fear of terrorism, while a large outgroup size is associated with lower fear of terrorism. Women hold greater fear than men, while commercial news consumption is associated with greater terrorism fears.